Implementation of Driving License Issuance Policy at Gowa Police Station - Sahabuddin Sahabuddin; Rifdan Rifdan; Haedar Akib; Sitti Hardiyanti Arhas (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2021)
A driver's license is proof of the legitimacy of competence, control tools, and police forensic data for someone who has passed the knowledge, ability, and skill test to drive a Ranmor on the road by the requirements specified under the Traffic and Road Transport Act. This study aims to determine the implementation of the policy of issuing a driving license at the Gowa Police Station in terms of resources; and the determinants of the policy implementation of the issuance of a Driving License (SIM in Indonesian) at the Gowa Police. This research method is qualitative with a phenomenological approach. The data sources used primary data through observation and interview instruments which determined nine research informants and secondary data through the review of various documents. The data analysis technique uses an interactive model, namely data collection, data condensation, data presentation, and verification/conclusion. The results of this study indicate that the policy for managing the issuance of SIM at the Gowa Police in terms of resources is not implemented properly, because there are still deficiencies in facilities and infrastructure that can provide a sense of comfort for SIM administrators when receiving services.